PERBANDINGAN IMPLEMENTASI MODEL PTK KEMMIS & MCTAGGART, KURT LEWIN, DAVE EBBUTT, DAN SUHARSIMI ARIKUNTO TERHADAP PENINGKATAN HASIL BELAJAR FISIKA SMA - Dani, Rahma; Phadila, Cindy Aulia (PMIPA FKIP UNJA, 2026)
This study aims to analyze and compare the implementation of four Classroom Action Research (CAR) cycle models in senior high school physics learning. The study employed a Systematic Literature Review (SLR) by examining articles from Google Scholar, SINTA, and Garuda published between 2020 and 2026. From 50 identified articles, the selection process resulted in 24 articles that met the criteria of two-cycle CAR studies in senior high school physics. Four representative articles were selected, each representing the CAR cycle models of Stephen Kemmis and Robin McTaggart, Kurt Lewin, Dave Ebbutt, and Suharsimi Arikunto, for comparative analysis. The results show that all models share a similar structure consisting of planning, action, observation, and reflection, but differ in the depth of reflection and improvement patterns between cycles. Operational-quantitative models tend to produce higher learning outcome improvements, while conceptual-reflective models provide more stable and contextual improvements. Quantitatively, the Suharsimi Arikunto model shows the most optimal improvement in learning outcomes, followed by the Kurt Lewin model.